2009
DOI: 10.1111/j.1399-0012.2009.00998.x
|View full text |Cite
|
Sign up to set email alerts
|

Pancreas after living donor kidney transplants in diabetic patients: impact on long‐term kidney graft function

Abstract: In this single-institution study, we compared outcomes in diabetic recipients of living donor (LD) kidney transplants that did vs. did not undergo a subsequent pancreas transplant. Of 307 diabetic recipients who underwent LD kidney transplants from January 1, 1995, through December 31, 2003, a total of 175 underwent a subsequent pancreas after kidney (PAK) transplant; 75 were deemed eligible (E) for, but did not receive (for personal or financial reasons), a PAK, and thus had a kidney transplant alone (KTA); a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 30 publications
(51 reference statements)
1
39
0
2
Order By: Relevance
“…12 While Kleinclauss et al did not find any difference between LDKA and PAK patients regarding patient and kidney survival rates, they observed that HbA1c and glomerular filtration rate (GFR) to be better in PAK cases. 13 In a study by Sampaio et al on the comparison of LDKA and PAK patients, both patient survival rate (75 versus 85%) and kidney survival rate (62 versus 75%) were determined to be better in the PAK group at the end of the 8-year follow-up. 14 In this study, kidney graft survival rates in KA, SPK, and PSK groups were 86.7, 95.2, and 97.1%, and patient survival rates were 96.7, 95.2, and 100%, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…12 While Kleinclauss et al did not find any difference between LDKA and PAK patients regarding patient and kidney survival rates, they observed that HbA1c and glomerular filtration rate (GFR) to be better in PAK cases. 13 In a study by Sampaio et al on the comparison of LDKA and PAK patients, both patient survival rate (75 versus 85%) and kidney survival rate (62 versus 75%) were determined to be better in the PAK group at the end of the 8-year follow-up. 14 In this study, kidney graft survival rates in KA, SPK, and PSK groups were 86.7, 95.2, and 97.1%, and patient survival rates were 96.7, 95.2, and 100%, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…Inexorable progression of diabetes is not uncommon and further endorgan complications may truncate the ability to proceed with PAK. Patients experiencing marked decrease in cardiac reserve or showing clear evidence of aortoiliac vascular disease will likely be denied further consideration of PAK [41].…”
Section: Timing For Pancreas Transplantmentioning
confidence: 99%
“…Improvement in recent outcomes in PAK and PTA through technical advances and more optimized immunosuppression mean that the comparative goalposts in pancreas and islet transplantation are constantly shifting [41,81]. Ideally, SPK provides effective therapy for both renal insufficiency and T1DM at once in a single procedure.…”
Section: Availability and Costmentioning
confidence: 99%
“…With increased frequency, this twostage procedure involves a living donor kidney transplantation followed by a cadaver pancreas transplant (PALK). This alternative has the advantage of a short waiting time and of a superior quality kidney graft (Kleinclauss et al, 2009). The second great advantage of PAK is performing major pancreas transplant surgery on a non-uremic patient.…”
Section: Pancreas After Kidney Transplantationmentioning
confidence: 99%